Riba and Justification in Practice in Scholars Views - Meirison, Meirison (Transformatif, 2018)
Abstract: Efforts have long been focused on trying to explain and justify riba (Usury) and dozens of theories have emerged in this area. This approach went to some Islamic economics writers, who also tried to justify and interpret interest in accordance with the principles of Islamic economics. This is one of the most important economic topics in the past and present, and although the writings on some of the elements of this subject began about half a century ago, but the observer renewed the introduction of these views and ideas in different formats in the present era, Islamic economics issues only show a picture of this subject for discussion. Therefore, this discussion aims to collect these opinions and theories and evaluate them in order to present them to the new discussioners - with different scientific backgrounds - in a suitable manner that serves to discuss this subject and clarify the general framework for it. This discussion will focus briefly on the presentation of some of these theories, opinions and justifications and discuss the hypotheses of these views and theories.Â Keywords: Riba, Justification